Pembentukan Karakteristik Religius Peserta Didik melalui Pembelajaran Aqidah Akhlak di MA NW Senyiur: Formation of Students' Religious Characteristics through Aqidah and Akhlak Learning at MA NW Senyiur - M. Alikarmani; Husnul Laili; Zainuddin (CV. Pendidikan Al-Gafari, 2026)
This study aims to describe the process of developing students’ religious character through Aqidah Akhlak learning at MA NW Senyiur. Religious character is a crucial component in education, especially in Islamic-based institutions, with the goal of shaping students into individuals who are faithful, morally upright, and behave according to Islamic teachings. This research uses a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The subjects of the study included Aqidah Akhlak teachers and students at MA NW Senyiur. Data analysis involved data reduction, data display, and conclusion drawing. The results showed that Aqidah Akhlak learning at MA NW Senyiur is conducted holistically, emphasizing not only cognitive aspects but also the development of attitudes and religious habits. Teachers play an active role as role models, motivators, and mentors in instilling religious values. Students’ religious character is reflected in their discipline in worship, politeness, honesty, and social concern. Supporting factors in this process include a religious school environment, regular religious programs, and active parental involvement. Challenges include the diverse backgrounds of students and the lack of consistent religious practice outside of school. Thus, Aqidah Akhlak learning plays a strategic role in shaping students’ religious character, which should continue to be strengthened through collaboration among schools, families, and the community.